2017
DOI: 10.5863/1551-6776-22.2.124
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Instability in an Infant Treated with Propranolol for Infantile Hemangioma

Abstract: Infantile hemangiomas are prevalent in the first few months of life and can be associated with risks of scarring, blindness, ulcerations, and airway obstruction depending on the location of lesions. Options for therapy include surgery, laser therapy, or medications. Propranolol is the only US Food and Drug Administration-approved medication option. Propranolol is a nonselective beta-blocker that crosses the blood-brain barrier because of its high lipophilicity, which increases the likelihood of central nervous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…On the one hand, reports of rare AE are very important so that when the phenomenon occurs, doctors can promptly reflect that it is caused by propranolol, thus allowing timely handling of the phenomenon; on the other hand, usage of propranolol as a treatment of IHs can be improved. For example, a report of dental caries suggested that sugar-free propranolol oral solutions are recommended for children [31]; propranolol may affect thermoregulation in infants, whereas atenolol may not [32].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, reports of rare AE are very important so that when the phenomenon occurs, doctors can promptly reflect that it is caused by propranolol, thus allowing timely handling of the phenomenon; on the other hand, usage of propranolol as a treatment of IHs can be improved. For example, a report of dental caries suggested that sugar-free propranolol oral solutions are recommended for children [31]; propranolol may affect thermoregulation in infants, whereas atenolol may not [32].…”
Section: Discussionmentioning
confidence: 99%
“…5,9 Previous case reports have shown that use of beta blockers in neonates especially preterm neonates is associated with hypothermia. 11,12 However maternal use of labetalol and its effect on neonatal thermoregulation have not been studied extensively. Labetalol like other beta blockers has been shown to cross placenta freely.…”
Section: Discussionmentioning
confidence: 99%
“…The common side effects (35,47) of propranolol include gastrointestinal discomfort, sleep disorders, agitation, and body temperature fluctuations. The serious ARs reported with propranolol treatment include atrioventricular block, bradycardia, hypotension, bronchospasm/bronchial hyperresponsiveness, and hypoglycemia.…”
Section: Oral Medications Beta-adrenergic Blocking Agents (β Blockers)mentioning
confidence: 99%